Influence of Company Image, Emotional Brand Attachment, and Perceived Value on Purchase Decisions of Customers of PT Dua Kelinci, Pati Regency - Indah Larasati; Makmun Riyanto; Sri Wahyuni (JOBS (Jurnal Of Business Studies), 2025)
Purchase decisions are a crucial factor that companies need to pay attention to because they play a role in building long-term relationships and increasing competitiveness. This is especially true for snack food companies such as PT Dua Kelinci, whose main focus is on customers. Therefore, maintaining purchase decisions is one of the keys to achieving the company's goals. This study aims to evaluate the impact of Company Image, Emotional Brand Attachment, and Perceived Value on Purchase Decision among PT Dua Kelinci customers. The research employs a quantitative method with data collection through the distribution of questionnaires to 100 respondents. Non-probability sampling was applied for sample selection, while data analysis was conducted using multiple linear regression. The results of the study indicate that, simultaneously, the three independent variables significantly influence the dependent variable, namely Purchase Decision. This finding implies that improving Company Image, Emotional Brand Attachment, and Perceived Value toward Purchase Decision can be an important strategy in enhancing PT Dua Kelinci's Purchase Decision